Hubungan Pengetahuan Remaja Dengan Perilaku Mestrual Hygiene di SMP Abulyatama Kabupaten Aceh Besar - Yuli Zuhkrina; Martina (Cahaya Ilmu Bangsa Institute, 2024)
Reproductive health is very important for humans, especially women. During menstruation, teenagers need to pay attention to menstrual hygiene to increase comfort in activities, self-confidence and not be shunned by friends because of the fishy smell. Ignorance of reproductive health can cause diseases such as pelvic inflammation, endometriosis and even infertility. The aim of this research is to see the relationship between adolescent knowledge and Mestrual Hygiene Behavior at Abulyatama Middle School, Aceh Besar Regency. This research is analytical research with a cross sectional approach. Sampling was carried out non-probability using a purposive sampling technique with the criteria being that class VII students were willing to be respondents and had menstruated. The results of this research were that of the 43 respondents, 23 (53.5%) had sufficient knowledge and 27 (62.8%) had negative Mestrual Hygiene behavior. In the bivariate analysis there is a p-value of 0.000 with a percentage of 100% of respondents who have less knowledge and have negative Mestrual Hygiene behavior. Negative adolescent Mestrual Hygiene behavior is greatly influenced by the knowledge that adolescents have so that they can maintain their hygiene and reproductive health. This activity is often ignored by teenagers because teenagers feel that this is not a necessity. Prolonged effects that can lead to long-term effects and can occur in teenagers who do not maintain hygiene during menstruation, namely infertility. Conclusion There is a very significant relationship between teenagers' knowledge and Mestrual Hygiene behavior at Abulyatama Middle School, Aceh Besar Regency with a p-value of 0.000